2023
DOI: 10.3390/ijms24033054
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Species Analysis Reveals Dysthyroidism of the Ovaries as a Common Trait of Premature Ovarian Aging

Abstract: Although the imbalance of circulating levels of Thyroid Hormones (THs) affects female fertility in vertebrates, its involvement in the promotion of Premature Ovarian Aging (POA) is debated. Therefore, altered synthesis of THs in both thyroid and ovary can be a trait of POA. We investigated the relationship between abnormal TH signaling, dysthyroidism, and POA in evolutionary distant vertebrates: from zebrafish to humans. Ovarian T3 signaling/metabolism was evaluated by measuring T3 levels, T3 responsive transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…THs can also affect the bioavailability of sex steroids by regulating SHBG [29]. Studies showed that the serum T3 and T4 values were positively correlated with the follicular triiodothyronine (T3) and thyroxine (T4) values [30,31]. Therefore, changes in serum THs levels, such as hypothyroidism and hyperthyroidism, may lead to ovarian hypofunction.…”
Section: Thyroid Hormones (Ths) Is Essential For Normal Ovarian Functionmentioning
confidence: 99%
“…THs can also affect the bioavailability of sex steroids by regulating SHBG [29]. Studies showed that the serum T3 and T4 values were positively correlated with the follicular triiodothyronine (T3) and thyroxine (T4) values [30,31]. Therefore, changes in serum THs levels, such as hypothyroidism and hyperthyroidism, may lead to ovarian hypofunction.…”
Section: Thyroid Hormones (Ths) Is Essential For Normal Ovarian Functionmentioning
confidence: 99%